The Influence of Health Education with Social Support Methods on Knowledge and Attitudes in Preventing Drug Abuse in Street Children Communities in Taman Bungkul Surabaya - Dewi, Nur Hidayahtul; Reliani, Reliani; Y, Fathiya Luthfil; Isnaini, Isnaini (Universitas Muhammadiyah Semarang, 2016)
Background: Street children are at risk when they are on the streets, such as using drugs, free sex, using tattoos, piercing, and being infected with HIV. Conditions such as lack of self-confidence, having unstable emotions, which are owned by street children, make them easily influenced by other people and tend to engage in anti-social behavior such as fighting, stealing, seizing, using Drugs (Alcohol, Psychotropic Narcotics, Addictive Substances) and running a drug business, and casual sex behavior.Purpose: to conduct research on the Effect of Health Education with Social Support Methods on Knowledge and Attitudes in Preventing Drug Abuse in Street Children Communities in Taman Bungkul Surabaya.Methods: Pre-experimental research design with one group pretest-posttest.Results: In the street children's group in Taman Bungkul Surabaya, the respondent's awareness of preventing substance abuse before and after obtaining health education has improved the category of knowledge and attitude from less to appropriate or nice. The attitude of street children before and after being given health education with social support methods in preventing drug abuse in the street children community in Taman Bungkul Surabaya has a mostly positive attitude change.Conclusion: There is an effect of health education with social support methods in preventing drug abuse in street children communities in Taman Bungkul Surabaya.